A North American Expert Opinion Statement on Sarcopenia in Liver Transplantation. Issue 5 (19th August 2019) - Carey, Elizabeth J.; Lai, Jennifer C.; Sonnenday, Christopher; Tapper, Elliot B.; Tandon, Puneeta; Duarte‐Rojo, Andres; Dunn, Michael A.; Tsien, Cynthia; Kallwitz, Eric R.; Ng, Vicky; Dasarathy, Srinivasan; Kappus, Matthew; et al.
Abstract : Loss of muscle mass and function, or sarcopenia, is a common feature of cirrhosis and contributes significantly to morbidity and mortality in this population. Sarcopenia is a main indicator of adverse outcomes in this population, including poor quality of life, hepatic decompensation, mortality in patients with cirrhosis evaluated for liver transplantation (LT), longer hospital and intensive care unit stay, higher incidence of infection following LT, and higher overall health care cost. Although it is clear that muscle mass is an important predictor of LT outcomes, many questions remain, including the best modality for assessing muscle mass, the optimal cut‐off values for sarcopenia, the ideal timing and frequency of muscle mass assessment, and how to best incorporate the concept of sarcopenia into clinical decision making. For these reasons, we assembled a group of experts to form the North American Working Group on Sarcopenia in Liver Transplantation to use evidence from the medical literature to address these outstanding questions regarding sarcopenia in LT. We believe sarcopenia assessment should be considered in all patients with cirrhosis evaluated for liver transplantation. Skeletal muscle index (SMI) assessed by computed tomography constitutes the best‐studied technique for assessing sarcopenia in patients with cirrhosis. Cut‐off values for sarcopenia, defined as SMI < 50 cm 2 /m 2 in male and < 39 cm 2 /m 2 in female patients, constitute the validated definition for sarcopenia in patients with cirrhosis. Conclusion: The management of sarcopenia requires a multipronged approach including nutrition, exercise, and additional pharmacological therapy as deemed necessary. Future studies should evaluate whether recovery of sarcopenia with nutritional management in combination with an exercise program is sustainable as well as how improvement in muscle mass might be associated with improvement in clinical outcomes.